1999
DOI: 10.1038/sj.cdd.4400509
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic correlation of apoptosis and immune activation during treatment of HIV infection

Abstract: T cells from HIV infected patients undergo spontaneous apoptosis at a faster rate than those from uninfected patients, are abnormally susceptible to activation induced cell death (AICD), and undergo increased apoptosis in response to Fas receptor ligation. These observations have led to the hypothesis CD4 T cell apoptosis may be a mechanism of CD4 T cell depletion and the pathogenesis of AIDS. Successful treatment of HIV infected patients is accompanied by quantitative and qualitative improvements in immune fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
59
0
1

Year Published

2001
2001
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(68 citation statements)
references
References 75 publications
8
59
0
1
Order By: Relevance
“…49,101 Interestingly, the enhancement in CD95-mediated T-cell death in rhesus macaques is not associated with either an upregulation of caspase-3 and caspase-8 or a decrease of FLIP-L and FLIP-S. Similarly, Badley et al 105 found that death of T cells from HIV-infected individuals was not associated with a change in the amount of FLIP. T-cell activation occurring in the course of immune responses has been shown to increase sensitivity to CD95-induced apoptosis.…”
Section: Activation-induced Cell Deathmentioning
confidence: 97%
See 1 more Smart Citation
“…49,101 Interestingly, the enhancement in CD95-mediated T-cell death in rhesus macaques is not associated with either an upregulation of caspase-3 and caspase-8 or a decrease of FLIP-L and FLIP-S. Similarly, Badley et al 105 found that death of T cells from HIV-infected individuals was not associated with a change in the amount of FLIP. T-cell activation occurring in the course of immune responses has been shown to increase sensitivity to CD95-induced apoptosis.…”
Section: Activation-induced Cell Deathmentioning
confidence: 97%
“…Antiretroviral therapy is followed by a significant decrease in CD95-induced, activation-induced, and spontaneous apoptosis in ex vivo cultured peripheral blood lymphocytes 60,96 which correlates with decreased immune activation. 105 Thus, effective viral suppression decreases immune activation and apoptosis, thereby contributing to immune reconstitution.…”
Section: Activation-induced Cell Deathmentioning
confidence: 99%
“…However, the levels of c-FLIP in purified CD4 þ and CD8 þ T cells from HIV þ donors do not differ from that of noninfected control donors. 110 The TNF/TNF receptors death pathway is also activated in HIV þ individuals, and both CD4 þ and CD8 þ T cells are susceptible to TNFR1-and TNFR2-induced apoptosis. 109 Susceptibility of patients' T cells to TNFR-induced apoptosis is associated with the downregulation of Bcl-2 protein, while there is no increased expression of the two TNFRs on the surface of T cells, and TNFR1-associated death domain (TRADD), receptor interacting protein (RIP) or TNF receptorassociated factor 2 (TRAF-2) expression is not altered by HIVinfection.…”
Section: Activation-induced Cell Deathmentioning
confidence: 99%
“…56 Rapid decreases of T-cell apoptosis after treatment with HIV protease inhibitors has been reported by several investigators. 57,58 Additional evidence supporting the critical role of apoptosis in AIDS progression emerges from studies in SIV-infected macaques where lymphocyte apoptosis was found to be associated with the pathogenicity of lentiviral infection. 31,32 Furthermore, an extensive apoptosis in peripheral lymphoid organs during primary SIV infection was previously found to be predictive of the ability of the immune system to control viral replication and disease progression.…”
Section: Apoptotic Defect Of Hiv-specific Cd8 þ T Cells Apoptosis Affmentioning
confidence: 99%
“…A previous study failed to show different expression of c-FLIP in purified CD4 þ and CD8 þ T cells from HIV-infected patients. 57 The expression of this molecule, however, in HIVspecific CD8 þ T-cell populations is not known. Similarly, the role of other factors regulating the CD95/Fas-induced apoptosis like FADD or Bid that has been described as the link between the Fas signaling and mitochondria 171 is also not known.…”
Section: Toward Understanding the Molecular Mechanism Of Hiv-specificmentioning
confidence: 99%